Performance evaluation and benchmarking for the era of cloud(s) : 11th TPC Technology Conference, TPCTC 2019, Los Angeles, CA, USA, August 26, 2019, Revised selected papers /: 11th TPC Technology Conference, TPCTC 2019, Los Angeles, CA, USA, August 26, 2019, Revised selected papers. (2020) - Unknown
No abstract available